Pengaruh Persepsi Tarif Pajak, Sanksi Perpajakan, Dan Penerapan Peraturan Pemerintah Nomor 23 Tahun 2018 Terhadap Kepatuhan Wajib Pajak - Salsa Pramudita; Wulandari Cahyani Putri (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of perceptions of tax rates, tax sanctions, and the implementation of government regulation number 23 of 2018 on taxpayer compliance. This type of research is quantitative research with primary data sources. The population in this research are UMKM business actors registered with the South Tangerang City Cooperatives and SMEs Service. The sample selection method used in this research was convenience sampling so that the final sample obtained using this method was 100 respondents. The data technique uses multiple regression analysis methods with the help of Microsoft Excel and SPSS Version 28 data processing. The research results simultaneously show that the variables of perception of tax rates, tax sanctions, and the implementation of government regulation number 23 of 2018 have a simultaneous effect on taxpayer compliance. Partially, it shows that the tax rate perception variable has no effect on taxpayer compliance. Furthermore, the tax sanctions variable influences taxpayer compliance. Meanwhile, the variable implementation of government regulation number 23 of 2018 has no effect on taxpayer compliance.